Work Motivation to Improve the Professionalism of Vocational Teachers with Teacherpreneur Character - Mahendra, Sena; Abdillah, Fuad; Ariwibowo, Bayu; Suyitno (Aspirasi Masyarakat Intelektual Islam Nusantara, 2025)
Work motivation is an important component in improving the professionalism of vocational teachers who possess teacherpreneur characteristics. Teachers are required to have more than technical expertise to meet the demands of the workforce in the Industrial Era 4.0. They must also demonstrate creativity, innovation, and entrepreneurial skills. The purpose of this study was to evaluate the influence of teachers’ work motivation and professionalism on the development of teacherpreneur characteristics. The research sample consisted of 264 productive teachers in the Automotive Vocational Technology field in Semarang City. The study employed a quantitative approach with an ex post facto research design. Path analysis and descriptive statistics were used to validate and analyze the questionnaire instruments. The results showed that work motivation had a significant direct effect on teacher professionalism (t = 4.69). The main conclusion is that increasing teachers’ work motivation positively contributes to the professional development of vocational teachers. This research highlights the importance of integrating entrepreneurial values into teacher development efforts within vocational education.